Numerical Scheme for Compartmental Models: New Matlab Software Codes for Numerical Simulation [version 2; peer review: 2 approved] - Samuel Akwasi Adarkwa; Samuel Okyere; Ebenezer Bonyah; Joseph Ackora-Prah (F1000Research, 2023)
Background: This paper presents a newly developed Matlab code for the numeri- cal simulation of compartmental/deterministic models. It addresses modeling and simulation issues concerning compartmental models. The code is easy to under- stand and edit for the simulation of compartmental models. An alternative codes for statistical software package R has been proposed for the same model. R software is freely available for use. Methods: We proposed a basic SEIR model for illustration purposes. Matlab and R software codes are developed for the SEIR model which users can follow and easily understand the computations. Results: The two codes work on all Matlab and R versions. For models with more compartments, we suggest using higher version of Matlab and R. Matlab works on windows, Mac and Linux Conclusions: New Matlab software codes purposely for numerical simulations of classical deterministic models which can run on any version of Matlab has been introduced in this paper. This code can be edited/modify to suit any deterministic models and any desired output required. An alternative open source free version has been written in R has been provided as well